Aloe vera in dentistry: current status and future prospects - ABU-SEIDA, Ashraf M. Abu-Seida; SEIF, Heba (International Arab Journal of Dentistry (IAJD), 2023)
This review declares the chemical composition, pharmacological actions, clinical applications, adverse reactions and future prospects of Aloe vera (AV) in the field of dentistry. Literature pertinent to Aloe vera in dental practice was explored in databases like PubMed, Scopus and Google Scholar. The relevant literature was reviewed and critically appraised in this review. Aloe vera is a miracle plant that has been applied as herbal therapy for thousands of years due to its multiple health benefits. In dental practice, AV has different applications and it attracts the attention of researchers due to its natural origin, low cytotoxicity, and various biological actions like anti-microbial, immunomodulatory, anti-inflammatory, antioxidant, wound healing, and antineoplastic actions. Therefore, it has been used for treatment of oral lesions, endodontic lesions, periodontal disease, oral wounds, and alveolar osteitis as well as in tissue engineering, reduction of plaque formation, decontamination of Gutta percha, around dental implants and others. AV has been used in treatment and prevention of several other oral and dental problems. Nevertheless, it has a lot to offer in the dental practice and future studies are recommended to maximize its beneficial role in the field of dentistry.